218 Maternal shift work during pregnancy and infant neurodevelopment parameters at eighteen months: results from taiwan birth cohort study. (24th April 2018) - Wei, Chihfu; Chen, Pau-Chung
Abstract : Introduction: Maternal shift work were found to be associated with altered sex hormone, pre-term delivery and small for gestational age. Previous studies also showed shorter breastfeeding duration among mothers with shift work. However, whether these adverse effects affect future infant neurodevelopment remained uncertain. Therefore, we aimed to find the association between maternal shift work status and children's neurodevelopment parameters. Methods: Taiwan Birth Cohort Study (TBCS) was the first nationwide birth cohort study in Taiwan that follows representatively sampled mother-infant pairs in 2005. The development and exposure condition of the participants were assessed by home interview with structured questionnaires upon six and eighteen months old. Propensity score matching was used to generate subpopulation with comparable characteristics. Multivariate logistic and Cox proportional hazard regression model were applied to examine the relative risk (RR) and hazard ratio (HR) between maternal shift work status and caregiver-reported neurodevelopment milestones. Results: In this study, 1751 term singletons were included in the propensity score matched cohort. Maternal shift work was associated with delay in care-giver reported gross motor neurodevelopment milestone, such as able to draw arbitrarily (RR=1.39, 95% confidence interval CI: 1.05 to 1.84; hazard ratio (HR)=1.13, 95% confidence interval CI: 1.02 to 1.25), able to drink with both hands (HR=1.11, 95% confidence interval CI: 1.00 to 1.23), and lower score in gross motor domain of TBCS development instrument (RR=1.41, 95% confidence interval CI: 1.01 to 1.96). However, the effects were attenuated after multivariate adjustment. Conclusion: This study showed possible associations between maternal shift work and delay in neurodevelopment milestone achievement at eighteen months. Although the associations were attenuated when adjusted for other parameters, further studies may be indicated to ascertain the association and the possible dose-response effect.